Effective thickness of timber elements for the evaluation of brittle failure in timber-to-steel connections with large diameter fasteners loaded parallel-to-grain at the elastic range: A new method based on a beam on elastic foundation. (15th April 2020) - Yurrita, Miguel; Cabrero, José Manuel
Highlights: Brittle failure of timber connections should be considered in the design. A new proposal to obtain the related timber element effective thickness is given. This method is based on a beam on elastic foundation model. The only considered parameter is the slenderness of the fastener. The results improve both the accuracy and the simplicity of the existing methods. Abstract: The consideration of brittle failure of timber connections requires an adequate evaluation of the capacity of the involved failure planes. Their correct geometrical definition is therefore of utmost importance to obtain an accurate assessment of their capacity. This article presents a new approach to account for the effective thickness of the lateral planes of timber members in connections with large diameter fasteners loaded parallel-to-grain when the fasteners remain in its elastic range, which allows to consider the uneven load distribution along the fastener in a simple way. The proposal is based on a fitting of a beam on elastic foundation model and only requires the slenderness of the fastener as a parameter. It provides a both simple and accurate way to calculate the effective thickness of timber elements.